(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
In the paper spatial distribution and dynamic change of number of days with precipitation 20 mm and more (shower) are clarified, analyzed and estimated. As a material have been used actual observations of precipitation at meteorological stations of Shirak. Have got close correlation link between height of area and number of days with precipitation 20 mm and more. The map of spatial distribution of annual number of days with precipitation 20 mm and more of studied area is made.